(Trans)gender stereotypes and the self: Content and consequences of gender identity stereotypes. Issue 4 (19th May 2021) - Howansky, Kristina; Wilton, Leigh S.; Young, Danielle M.; Abrams, Samantha; Clapham, Rebekah
ABSTRACT: Transgender individuals experience stigmatization through the application of gender stereotypes. In Study 1, cisgender individuals (N = 212) produced unique stereotypes, such as "mentally ill" and "confused, " about transgender, but not cisgender, populations. Stereotypes for transgender individuals also included stereotypes related to both cisgender men and cisgender women. In Study 2, transgender people (N = 330) rated the unique stereotypes about their group more negatively than cisgender people (N = 193) rated the same stereotypes. These data highlight distinct ways that transgender people, who represent one of the most stigmatized social groups, experience stigma through stereotype application. Discussion includes how research including nontraditional gender identities broadens and advances diversity and identity science.